Circulation and the Shift of Political Dynasties: Instrumentalization of the Golkar Party in Local Politics in Banten - Imron Wasi (Universitas Brawijaya, 2026)
The circulation of local elites and shifts in political power in Banten became evident in the 2024 regional elections, which marked the decline of the Tubagus Chasan Sochib political family, historically associated with the Golkar Party. This study examines changes in power relations among political dynasties, parties, and actors using a case study approach based on secondary data from documents, reports, and mass media sources. The findings show that Golkar functioned as a political instrument for the Banten political dynasty in maintaining power, while elite circulation largely occurred within political dynasties through familism and quasi-familism. In the post-reform era, the dynasty and Golkar mainly dominated executive offices, with Airin Rachmi Diany representing the continuation of the Tubagus Chasan Sochib family's influence through quasi-familial ties. However, the defeat of the Airin–Ade pair reflected a shift in power dynamics driven by support from national elites and political parties aligned with the Prabowo Subianto–Gibran Rakabuming Raka coalition. Consequently, elite power in Banten shifted from the Tubagus Chasan Sochib political family to the Dimyati Natakusumah political family.